BFC Method For Prediction of Transient Head on Seepage Path - Sherly Hartono (Bina Nusantara University, 2010)
Seepage causes weakening of levees and can cause levee failure or overtopping due to levee settlement. A numerical method, called the boundary fitted coordinate (BFC) method, was developed to determine seepage through a levee and the transient head on the seepage path due to the changing water level during a flood. The BFC transforms the physical coordinate system into a computational curvilinear coordinate system. The grid generated in this method accurately represents the boundary of the system regardless of its complexity.